Strategies to Improve Drug Compliance Among Patients with Mental Disorders: A Systematic Review - Jakkulin Lilly Priya C. (International Journal of Evidence Based Nursing And Practices, 2025)
Background: Mental disorders constitute a public health concern, accounting for 13% of the global disease burden. Pharmacotherapy along with psycho education is primary line of treatment and maintaining drug compliance is crucial. Aim: The aim of this systematic review was to summarize the strategies to improve drug compliance among patients with mental disorders, identify which tools are most frequently used to measure strategies to improve drug compliance among patients with mental disorders and report on outcomes of strategies to improve drug compliance among patients with mental disorders. Method: In accordance with PRISMA guidelines, we conducted a search for articles indexed in PubMed, PsycINFO, Web of Science, and CINAHL databases using a combination of keywords such as "Strategies" AND "Drug Compliance" OR "Mental Disorders". Results: Five empirical studies were identified as pertinent to our research. Various tools were employed to assess strategies aimed at improving drug compliance in patients with mental disorders. The findings indicated that factors such as gender, education level, marital status, occupation, type of medication prescribed, patient insight, complex medication regimens, delayed onset of effects, and the unavailability of medication played a significant role in influencing drug compliance. The motivational interviewing is to improve drug compliance in incentivizing, motivating and maintaining the change in people’s behavior and cognitive-behavioral approach determinants, the lack of compliance like lack of insight and rejection of treatment, and dissatisfaction with medication. Conclusions: This review underlines the strategy to improve drug compliance among mental disorders patients with motivational interviewing and cognitive-behavioral approach. Enhancing medication adherence in individuals with mental illnesses has the potential to reduce both the morbidity and the suffering experienced by patients and their families.
Keywords: Drug compliance; Medication; Mental Disorders; psycho education; strategies